Sub-200 fs Polarization-Maintaining All-Fiber Thulium-Doped Dissipative Soliton Fiber Laser System at 1920 nm - Timothy Lim; Shutao Xu; Lachlan Hooper; Maria Davey; Michelle Y. Sander (Photonics)
A polarization-maintaining all-fiber laser source based on a nonlinear amplifying loop mirror with broadband operation (64 nm) around 1920 nm is demonstrated. The oscillator can generate 66 pJ up-chirped dissipative soliton pulses at a repetition rate of 22.8 MHz with a high polarization extinction ratio of 17 dB. By adding a polarization controller to the polarization-maintaining dispersion-compensating fiber, the filter behavior can be adjusted allowing for the tuning of the emission to a center wavelength of 1878 nm, 1907 nm, and 1926 nm. Using an all-polarization-maintaining single-mode fiber amplifier with anomalous dispersion, the pulses are amplified to 0.9 nJ and compressed to a near Fourier-limited pulse duration of 170 fs with a peak power of 4.3 kW. Such all-fiber-based sources are attractive due to their compact size, high beam quality, and good environment stability.